Digitization of Oral Literature and its Problems in Literature Learning in Schools - Oktavia Winda Lestari; Ilmia Turrofiah; Siti Zumrotul Maulida (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: Oral literature is one of the learning materials in schools. With the development of today's technology, bringing oral literature to a more modern world. The digitization of literature makes it easier for teachers to convey the essence of oral literature to students. However, with the digitization of oral literature, various problems have arisen. This research aims to explain various problems that occur in oral literature that is packaged in digital form. The method used is a qualitative descriptive method with a literature approach. The researcher collected data through the results of the analysis of various print media. From the results of the research, there are three problems that occur, including, 1) Oral literature that is converted into digital form can reduce the values of oral literature itself, 2) Oral literature consists of various elements, one of which is the flexibility of the storyteller. When oral literature is converted into video form, the flexibility of the storyteller will be frozen in the video. The taste and atmosphere created will also be different when oral literature is delivered in live performances and through videos, and 3) the digitization of oral literature that is not conveyed in accordance with the authentic work, can reduce the authentic values of oral literature itself which will later affect students' understanding. Keywords: digitization of oral literature, problematic, and literary learning in schools.